Activation of group I metabotropic glutamate receptors leads to brain-derived neurotrophic factor expression in rat C6 cells - Kittikun Viwatpinyo (2018)
Brain-derived neurotrophic factor (BDNF), which mediates neuronal growth, neuroprotection and synaptic modulation, is expressed in neurons and glial cells. The present study investigated the expression of BDNF in response to the activation of group I metabotropic glutamate receptors (mGluRs) by (S)-3,5-Dihydroxyphenylglycine (DHPG) in rat C6 glioma cells. The increase in BDNF mRNA in DHPG-stimulated cells, which peaked by 12 h after DHPG exposure, was attenuated by the mGluR5 inhibitor MPEP, but not by the mGluR1 inhibitor CPCCOEt. DHPG-induced BDNF mRNA expression reduced in cultures pretreated with protein kinase C (PKC) inhibitor, GFX, but not with calcium/calmodulin kinase II (CaMKII) inhibitor, KN-93. Immunostaining revealed high BDNF expression in cytoplasm of C6 cells after 48 h of incubation with 1 μM DHPG, but this was lower in MPEP-pretreated cells. These results indicate that activation of group I mGluRs induces BDNF mRNA and protein expression via mGluR5 subtype and PKC-dependent signaling pathway in C6 glioma cells. © 2009 Elsevier Ireland Ltd. All rights reserved.